IMPLEMENTASI TEKNOLOGI DALAM MANAJEMEN SUMBER DAYA MANUSIA: TANTANGAN DAN PELUANG DI ERA DIGITAL - Hanifah Hanifah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
In the fast-paced and ever-evolving digital landscape, the integration of technology has become an indispensable aspect of various facets of life, and notably, in the realm of human resource management (HRM). This article endeavors to delve into the multifaceted terrain of challenges and opportunities encountered by organizations in the implementation of technology within HRM. We analyze the impact of technology on HRM functions, such as recruitment, training, performance management, and employee retention. In addition, we discuss strategies that organizations can adopt to overcome the challenges that arise and take advantage of the opportunities offered by technology in HRM. Ultimately, integrating technology into HRM is a complex process with both obstacles and advantages. This article seeks to enhance comprehension of technology's impact on HRM by examining its relationship with key functions and providing solutions to challenges. As businesses adapt to the digital landscape, making informed decisions and implementing proactive strategies are crucial to ensuring technology enhances HRM rather than hinders it in the modern era.